The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/ppul.25115
|View full text |Cite
|
Sign up to set email alerts
|

Randomized pilot trial of ipratropium versus placebo in children with critical asthma

Abstract: Objective To test the effects of inhaled ipratropium on clinical outcomes of critical asthma in the first randomized trial of this adjunctive therapy in critically ill children. Design Pilot, placebo‐controlled, double‐blinded, and randomized‐controlled trial Patients Thirty children (15 per group) with critical asthma receiving high‐intensity albuterol per a standardized pathway utilizing objective assessments to wean patients to less frequent albuterol administration. Interventions Subjects were randomized t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Previous studies [16][17][18] concentrate on the impact of the addition of IB in hospital length of stay, proving that IB does not reduce days of hospital admission. However, there is no previous literature concerning its impact on the length of stay at the PED.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies [16][17][18] concentrate on the impact of the addition of IB in hospital length of stay, proving that IB does not reduce days of hospital admission. However, there is no previous literature concerning its impact on the length of stay at the PED.…”
Section: Discussionmentioning
confidence: 98%
“…10 One single-center, double-blinded, randomized, controlled trial of 30 children requiring PICU admission for either continuous or hourly albuterol treatments addressed this question. 11 Investigators found no significant difference in duration of high-intensity albuterol, PICU length-of-stay, or hospital length-of-stay between those who continued to receive ipratropium bromide in the PICU and those who did not. This finding is consistent with previous studies analyzing ipratropium bromide given to asthmatic children hospitalized in the general ward.…”
Section: Asthma Exacerbations and Severe Asthmamentioning
confidence: 99%
“…The drug ipratropium bromide has been shown to decrease rates of hospitalization in children with asthma when given alongside systemic steroids and inhaled beta‐agonists in the emergency department, yet there have been no trials assessing the effect of ipratropium bromide use in critically ill asthmatics admitted to the pediatric intensive care unit (PICU) 10 . One single‐center, double‐blinded, randomized, controlled trial of 30 children requiring PICU admission for either continuous or hourly albuterol treatments addressed this question 11 . Investigators found no significant difference in duration of high‐intensity albuterol, PICU length‐of‐stay, or hospital length‐of‐stay between those who continued to receive ipratropium bromide in the PICU and those who did not.…”
Section: Asthma Exacerbations and Severe Asthmamentioning
confidence: 99%
“…It is in this environment that a study such as Dr. Murphy's is impressively conducted 6 . Performing clinical trials of status asthmaticus in children at a single center requires a sustained effort over several asthma seasons.…”
mentioning
confidence: 99%
“…In this issue of Pediatric Pulmonology , Murphy et al 6 conducted a randomized double‐blinded placebo‐controlled trial of ipratropium in children with critical asthma. Children were randomized to receive either ipratropium or placebo until they had been weaned to intermittent albuterol therapy every 2 h. This study, which stretched over 3 years, found no improvement in outcomes in the group that received ipratropium including similar hospital and PICU length of stay and similar time until spaced to every 2‐h albuterol.…”
mentioning
confidence: 99%